PENGARUH PUPUK KASCING DAN PUPUK NPK TERHADAP PERTUMBUHAN BIBIT TANAMAN KAKAO (Theobroma cacao L.) - Febrianti Triastuti; Wardati '; Arnis En Yulia (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This research aims to determine the interaction of vermicompost and NPK fertilizers as well as get the best dose of the growth of cocoa seedling (Theobroma cacao L.). This research has been conducted on the experimental field of the Faculty of Agriculture, University of Riau from April to August 2015. The study was conducted in 4 x 4 factorial experiment arranged in completely randomized design. The first factor is the dose of vermicompost that consists of 4 levels:          0 g/plant, 15 g/plant, 25 g/plant and 35 g/plant and the second factor is the dose of NPK fertilizer which consisting of 4 levels: 0 g/plant, 7,5 g/plant, 15 g/plant and 22,5 g/plant. In this study, there are 16 combinations of treatment with 3 replications so that there are 48 experimental units. Each experiment contained 3 unit seedling and two nursery plants into samples so obtained total 144 seedlings. Observations was plant heigh, number of leaves, stem diameter, leaf area, root volume, the ratio of crown roots and dry weight of plants. The results showed that the interaction of vermicompost and NPK fertilizers give the best effect at treatment of vermicompost 25 g/plant and NPK fertilizer 7,5 g/plant. Vermicompost best factor is 15 - 25 g/plant, while the factor that best NPK fertilizer is 7,5 g/plant. Keywords: Theobroma cacao L., vermicompost, NPK fertilizer